Angelica o la notte di maggio di Alberto Savinio. Le tecniche dello straniamento tra fantastico e surrealismo - Giancarlo Riccio (Between, 2022)
In this essay, we take into consideration the relationship between the concept of “phantasmic” developed by Savinio in his writings on art, that of “marvelous” proposed by Breton (compared with various definitions of the fantastic), and the dissolution of the traditional novel carried out in Angelica or the night in May (1927). Thus, we aim to analyze some stylistic and narrative techniques through which the alienating process is implemented in the writing of Savino. Attention is focused, above all, on issues and forms related to the questioning of optical-perspective normality and on the relationships between alternative reality paradigms. Finally, an attempt is made to develop a satisfactory interpretation of Savinio’s anti-novel through a comparison with Sklovsky’s reflections in order to highlight its structural ambiguity.